Making sense out of missense mutations: Mechanistic dissection of Notch receptors through structure‐function studies in Drosophila - Yamamoto, Shinya (Development, growth & differentiation, 2020)
Notch signaling is involved in the development of almost all organ systems and is required post‐developmentally to modulate tissue homeostasis. Rare variants in Notch signaling pathway genes are found in patients with rare Mendelian disorders, while unique or recurrent somatic mutations in a similar set of genes are identified in cancer. The human genome contains four genes that encode Notch receptors, NOTCH1‐4, all of which are linked to genetic diseases and cancer. Although some mutations have been classified as clear loss‐ or gain‐of‐function alleles based on cellular or rodent based assay systems, the functional consequence of many variants/mutations in human Notch receptors remain unknown. In this review, I will first provide an overview of the domain structure of Notch receptors and discuss how each module is known to regulate Notch signaling activity in vivo using the Drosophila Notch receptor as an example. Next, I will introduce some interesting mutant alleles that have been isolated in the fly Notch gene over the past > 100 years of research and discuss how studies of these mutations have facilitated the understanding of Notch biology. By identifying unique alleles of the fly Notch gene through forward genetic screens, mapping their molecular lesions and characterizing their phenotypes in depth, one can begin to unravel new mechanistic insights into how different domains of Notch fine‐tune signaling output. Such information can be useful in deciphering the functional consequences of rare variants/mutations in human Notch receptors, which in turn can influence disease management and therapy. Missense alleles in the fly Notch gene isolated over the past > 100 years of research have facilitated the understanding of Notch biology. By identifying unique alleles of the fly Notch gene through forward genetic screens, mapping their molecular lesions and characterizing their phenotypes in depth, one can begin to unravel new mechanistic insights into how different domains of Notch fine‐tune signaling output. Such information can be useful in deciphering the functional consequences of rare variants/mutations in human NOTCH receptors, which in turn can influence disease management and therapy.